Internal hernia in late pregnancy after laparoscopic Roux-en-Y gastric bypass. (23rd December 2014) - Gruetter, Florian; Kraljević, Marko; Nebiker, Christian A; Delko, Tarik
Abstract : A 27-year-old patient in late pregnancy presented to the department of obstetrics with crampy abdominal pain located in the right flank, 3 years after a laparoscopic Roux-en-Y gastric bypass. Clinical investigation showed tenderness on palpation in the upper abdomen without signs of peritonitis. The cardiotocogram and blood tests were normal. The ultrasound showed a hydronephrosis on the right side, and a pigtail catheter was inserted. The abdominal symptoms did not abate and the abdominal surgeon was consulted 36 hours after admission. Diagnostic laparoscopy was performed promptly because of high suspicion of internal hernia (IH). Laparoscopy showed IH at the mesojejunal intermesenteric defect with a herniated common channel and volvulus of the anastomosis. Conversion to open reduction and complete closure with non-absorbable interrupted sutures was performed. Small bowel resection was avoided. The patient was discharged 10 days after the operation and a healthy boy was born 4 weeks later.